Sosialisasi Kesetaraan Gender untuk Membangun Kesadaran Hak Anak Sejak Dini Bagi Anak-Anak di Sanggar Kreativitas Anak PKPA - Afifah Azzahra; Salsabilah Syifa Siregar; Mayang Febi Awaliyah; Hairani Siregar (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
Gender equality education has emerged as a key focus in raising knowledge of children’s rights from a young age. This article describes how the Center for Child Protection and Studies (PKPA) uses community, parent, and child involvement in educational programs to promote gender equality. The primary goal, particularly in Indonesia, is to establish a welcoming, equitable, and gender-neutral atmosphere. By using a participative, local wisdom-based approach, this program was able to change community perceptions, overcome gender stereotypes, and raise children’s understanding of their rights. In addition to raising awareness of gender equality issues among the younger generation, this outreach hopes to spark larger social change. With the cooperation of many stakeholders, the PKPA program has developed into a viable model for building an inclusive and equitable society.